A long-term vegetable crop rotation study to determine effects on soil microbial communities and soilborne diseases of potato and onion. Issue 1 (2nd January 2017) - Wright, Peter J.; Falloon, Richard E.; Hedderley, Duncan
ABSTRACT: A rotation trial spanning nine consecutive growing seasons was established in 2004 to study cumulative effects of specific onion- and potato-focused crop rotations on soil nutrient levels, soil biological communities, plant productivity and soilborne diseases. Soil microbial activity, as determined by fluorescein diacetate hydrolysis, was greatest in the 'sustainable' potato rotation in five of the 6 years that the test was carried out. Rhizoctonia solani anastomosis group 3 DNA was first detected in potato monoculture soils in the fifth year, with numbers increasing from then on, but was not detected in the onion monoculture throughout the trial period. Potato yields were greater when a crop other than potato was grown in the previous year compared with when potatoes were the preceding crop. After 2005, mean annual onion yields from the onion monoculture were less than yields from the other rotations. Black scurf on potato tubers was the primary soilborne disease observed during the study, and the incidence of this disease was greater in the potato monoculture than the other rotations after the second year, and least when potatoes had not been grown in the same ground the three previous seasons. This long-term crop rotation study has demonstrated the benefits of a 'sustainable' rotation where potatoes or onions were grown every fourth growing season, with different crops (oat, broccoli, cabbage, squash) grown in the intervening years, compared with the conventional consecutive biennial crops of potato and onion.